PEMASYARAKATAN HASIL PENELITIAN ARKEOLOGI: SEBUAH KERANGKA - Riyanto, Sugeng (Berkala Arkeologi, 2003)
It is appropriate if activities such as the publication of archaeological research results, exhibitions, scientific meetings, or other forms of publication are categorized as "socialization" results of archaeological research. Basically, these activities are an effort to inform the results of archaeological research to the public. But of course the goal is not just to provide information regardless of whether the effect is as expected and planned. Meanwhile information becomes operational through communication. Therefore it is important to view and place the socialization results of archaeological research within the framework of the principles of communication.